Farm Aid: a Case Study of a Charity Rock Organization - (:unkn) unknown (My University, 2016)
This study examines the impact that the non-profit organization Farm Aid has had on the farming industry, policy, and the concert realm known as charity rock. This study also examines how the organization has maintained its longevity. By conducting an evaluation on Farm Aid and its history, the organization’s messaging and means to communicate, a detailed analysis of the past media coverage on Farm Aid from 1985-2010, and a phone interview with Executive Director Carolyn Mugar, I have determined that Farm Aid’s impact is complex and not clear. Farm Aid, while very active in the political sphere, including lobbying for certain reforms, has not had a direct impact on policy. Furthermore, this study has shown that Farm Aid has been able to maintain its longevity by changing its messaging and mode of communication as well as aligning itself with a shift in food culture that promotes healthy food. Lastly, I will show how Farm Aid is an example of a successful charity rock organization that has raised both awareness and money without achieving the main goal: altering policy.
Keywords: Charity Rock; Consumer Politics; Farm Aid; Public Policy; Willie Nelson